Analysis of the External Conflict of the Main Character in the “Don’t Look Up” Movie - I Gusti Ngurah Aditya Pranandha Swijana; I Putu Andri Permana (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The study aims to identify literature, especially the inherent components restricted to the type of conflict and the strategy for managing conflicts. in the movie named “Don’t Look Up”. The qualitative descriptive method is used for the research method to provide a well-organized description; this method was used because it briefly explained the findings and aimed to recognize the varieties of conflict and strategies for managing conflicts efficiently. The data collection for this study employed the observational method, conducted across four distinct stages, namely; watching the “Don’t Look Up” movie repeatedly to ensure an understanding of the conflict, note-taking by listing the types of conflict and their resolution, selecting each data that has rich of information regarding the conflict and conflict management strategies, and classifying each data that related with the problem conflict in the “Don’t Look Up” movie. The research identified external conflicts, specifically involving interpersonal conflict (man vs. man) and conflict with the natural environment (man vs. nature), it is because most of the conflict in this movie is related to outside forces that made the main character “Randall” face the conflict and resolve each of the conflict. The conflict management strategy found avoidance in the “Don’t Look Up” Movie. This study intends to enhance the literary studies theory and present valuable concepts that can aid in comprehending character building especially related to conflict and conflict management strategies